ТАЛАБАЛАР ОНГИДА МОДДИЙ ВА МАЪНАВИЙ ҲАЁТ УЙҒУНЛИГИНИ ШАКЛЛАНТИРИШ АСОСЛАРИ (Scientific journal of the Fergana State University, 2023)
In the article the problems of development of the competence of the future teachers and also mastering by the professional competence for conducting successful activity are stated.